KAJIAN LIMBAH SENTRA RUMAH KAYU MINAHASA DI DESA TOMBASIAN ATAS - Recard Wowor; Maria Sumakud; Hengki Walangitan (COCOS, 2019)
ABSTRACKSTUDY OF MINAHASA WOOD SENTRA WASTE IN THE TOMBASIANVILLAGEThis study aims to describe the shape and amount of waste produced in themanufacture of Minahasa wooden houses, especially sawdust waste. This researchwas conducted at the center of the wooden house industry Tombasian Village, Kec.Kawangkoan Barat, Minahasa Regency. The study was conducted for approximatelythree months from November 2019 to January 2020. This research was conducted byquestionnaire survey method and direct measurement. The results of the amount ofwaste can be seen that the amount of raw material used for the construction of a 6 x5.5 m type house is approximately 6382733 cm3 after the process is seized to5571466 cm3. generated 811308 cm3 or 12.72%, thus the waste processed by thebulkhead is classified as large.ABSTRAK